Analysis of Market Requirements in the Field of Information Technology in Libya - Saad A. Al Deeb; Mohammed F. Al Boashi (Surman Journal of Science and Technology, 2024)
Continuous changes in advanced information technology contribute to exacerbating the shortage of IT professionals in both the public and private sectors. The types of skills required from IT professionals are also directly affected by these technological changes. This study aims to identify the various skills demanded from IT professionals [1]. As part of this study, we conducted a comprehensive analysis of the Libyan labor market by distributing a set of questionnaires to Libyan state institutions. These questionnaires were designed to gather precise information regarding the market's needs for skills and expertise. The results indicate significant challenges related to graduates' qualifications and the availability of training opportunities, necessitating the enhancement of training and professional development programs. Clear trends toward the use of specific technologies in various fields, such as artificial intelligence, data analysis, and information security, are also evident. These findings provide important insights for educational institutions and the job market, helping to improve the alignment of skills with market needs. Therefore, it is essential to invest in the development of new training programs that align with rapid technological changes and meet the ever-evolving requirements of the labor market. Improving the quality of education and training in this field will enhance graduates' opportunities and increase their competitiveness in the job market.